Effect Of Immersion Of Used Cooking Oil With Activated Charcoal Bagasse (Saccharum officinarum) On Free Fatty Acids - Febriana Ramadhani; Purwati (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2022)
Background: Used cooking oil is a cooking oil that has been declining its quality. One way to improve the quality of used cooking oil is by adsorption using bagasse charcoal as an adsorbent.. Objectives: The purpose of the study was to determine the effect of soaking used cooking oil with bagasse activated charcoal (Saccharum officinarum) on free fatty acid levels.. Research Metodes: This study uses an experimental design with descriptive data analysis and sampling technique using quota sampling. Determination of free fatty acid levels using the Alkalimetry method. Results: The free fatty acid content before immersion was 0.33% and the free fatty acid content after soaking was 0.5 hours, 24 hours, 48 ​​hours and 72 hours as follows: 0.3225%; 0.2967%; 0.2941%;0.2790%. The percentage decrease in free fatty acid levels occurred in the 72-hour immersion, which was a decrease of 15.33%. Conclusion: Based on the results obtained, it can be concluded that there is an effect of soaking bagasse activated charcoal (saccharum officinarum) on free fatty acids in used cooking oil. The longer the soaking time of activated charcoal bagasse (saccharum officinarum) in used cooking oil, the less free fatty acid content obtained. Keywords: Activated charcoal, used cooking oil, free fatty acids